De la mirada al registro - González Biffis, Julieta (2018)
Each one constructs his own image based on his perception, defined by the personal way of seeing, which will be captured with the use of different types of records. In this sense, the drawing is for the architect, designer or urban planner, the language to communicate their ideas and concerns. In the teaching of our discipline, thesketch is a tool of constant use. In this framework, the work proposes a reflection on the challenging path that is generated in each individual from the moment of observation to the elaboration of the graphic record.